2017
DOI: 10.3345/kjp.2017.60.7.208
|View full text |Cite
|
Sign up to set email alerts
|

Association of Toll-like receptor 2-positive monocytes with coronary artery lesions and treatment nonresponse in Kawasaki disease

Abstract: PurposeActivation of Toll-like receptor 2 (TLR2) present on circulating monocytes in patients with Kawasaki disease (KD) can lead to the production of proinflammatory cytokines and interleukin-10 (IL-10). We aimed to determine the association of the frequency of circulating TLR2+/CD14+ monocytes (FTLR2%) with the outcomes of KD, as well as to compare FTLR2% to the usefulness of sIL-10.MethodsThe FTLR2% in patients with KD was measured by flow cytometry. Serum levels of IL-10 (sIL-10) were determined in 31 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Mounting evidence has indicated that the regulation of toll-like receptors participates in the pathogenesis of KD ( 30 ) by stimulating neutrophil migration ( 31 33 ). More importantly, both neutrophil migration and transformation were associated with shock syndrome, a refractory response to IVIG and coronary artery lesions (CAL) in KD ( 34 36 ). Neutrophil activation has been reported to be enhanced with a marked increase in ROS, which contributes to the excessive formation of neutrophil extracellular traps (NETs), which has been suggested as being involved in the pathogenesis of KD ( 31 , 37 39 ), as well as the severity of acute respiratory syndrome caused by SARS-CoV-2 and severe COVID-19 patients who have cardiovascular injuries ( 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has indicated that the regulation of toll-like receptors participates in the pathogenesis of KD ( 30 ) by stimulating neutrophil migration ( 31 33 ). More importantly, both neutrophil migration and transformation were associated with shock syndrome, a refractory response to IVIG and coronary artery lesions (CAL) in KD ( 34 36 ). Neutrophil activation has been reported to be enhanced with a marked increase in ROS, which contributes to the excessive formation of neutrophil extracellular traps (NETs), which has been suggested as being involved in the pathogenesis of KD ( 31 , 37 39 ), as well as the severity of acute respiratory syndrome caused by SARS-CoV-2 and severe COVID-19 patients who have cardiovascular injuries ( 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that toll-like receptors, particularly toll-like receptor 2 (TLR2) is associated with the development of KD. In human patients with KD, increased expression of TLR2 positive CD14 monocytes occurs in the acute phase of KD (22), and is down regulated after IVIG therapy (30), and can successfully predict risk of coronary artery lesions and IVIG resistance (31). In mouse models of KD, mice which were TLR2 or MyD88 deficient failed to develop KD after induction by Lactobacillus casei cell-wall extract (LCCWE), suggesting that TLR2 signaling through the MyD88 pathway is crucial for the development of KD (32).…”
Section: Discussionmentioning
confidence: 99%
“…The typical treatment for this disease is a single intravenous injection of immunoglobulin (IVIG) at a dose of 2 g/kg in combination with oral aspirin, which reduces the chances of coronary artery damage to 5% 2 . Moreover, the incidence of coronary artery damage is high in patients with IVIG resistance 4 , with approximately 10–20% of patients experiencing coronary artery damage 5 . Thus, this condition requires clinician attention and effective treatment to resolve the inflammatory process and improve patient prognosis.…”
Section: Introductionmentioning
confidence: 99%